Composition for biomimetic material as well as preparation method and product thereof

By mixing the bionic material composition with hydrogenat hydroxyl hydrogen, polyal acid, and super -diverticate polymers, the problem of lactic acid bionic material is insufficient and rough on the surface of the bionic acid bionic material, and the material is achieved. High mechanical performance, good biocompatibility and suitable processing performance.

CN119345457APending Publication Date: 2025-01-24ZHEJIANG HISUN BIOMATERIALS

Patent Information

Application Number
CN202411482978.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The application of polylactic acid-based bionic materials in bone tissue engineering is limited by problems such as insufficient toughness and rough surface, which affects its processability and performance.

Method used

The hydrophobic hydroxyl hydroxylite, polylactic acid, and hypertext polymer with hypertrophic polymerization and polycophane as the arm are mixed together.

Benefits of technology

It improves the mechanical toughness, biocompatibility and biodegradability of the material, improves the compatibility and decentralization of the material, reduces the contraction rate of the material, and is suitable for 3D printing technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119345457A_ABST
    Figure CN119345457A_ABST
Patent Text Reader

Abstract

The invention relates to a composition for a biomimetic material and a preparation method of the composition. The composition comprises hydrophobic modified hydroxyapatite, polylactic acid and a hyperbranched star polymer with a hyperbranched polymeric structure as a core and polycaprolactone as an arm. The invention also relates to a product containing the composition for the biomimetic material. According to the application, the hyperbranched star-shaped polymer taking a hyperbranched polymerization structure as a core and polycaprolactone as an arm is creatively introduced into a PLA / HA composite system, and the hyperbranched star-shaped polymer can effectively improve the compatibility among the components and also can reduce the shrinkage rate of the composition for the biomimetic material. The composition for the biomimetic material can be processed to prepare a 3D printing wire rod with good toughness and high surface quality. According to the 3D printing wire rod, through the 3D printing technology, the manufactured bionic support is good in mechanical performance and size stability, and the printing process is smooth.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and specifically relates to a bionic material composition, a preparation method thereof and a product thereof. Background Art

[0002] For the treatment of bone defects, autologous bone transplantation has the advantages of high biocompatibility, good osteoconductivity and osteoinductivity, high bone healing rate, etc. However, in the process of autologous bone transplantation, there are also many problems that are difficult to overcome, such as limited sources of autologous bone, the need for additional surgery, and the donor site is prone to infection. Therefore, it is of great significance to develop bionic scaffolds with excellent performance.

[0003] The ideal biomimetic bone scaffold has excellent biocompatibility and biodegradability, mechanical strength similar to that of bones, good hydrophilicity and osteogenic differentiation ability, etc. Polylactic acid (PLA) has excellent biocompatibility and biodegradability, but the high brittleness, high hydrophobicity and limited biological activity of PLA itself have limited the clinical application and in-depth development of single PLA in bone tissue engineering.

[0004] Hydroxyapatite (HA) is the main inorganic component of human bones and can promote the adhesion and proliferation of osteoblasts. Incorporating HA into the polymer matrix can enhance the hydrophilicity and bioactivity of PLA-based materials.

[0005] CN116350851A discloses a bone defect repair material and a preparation method and use thereof, wherein the bone defect repair material is prepared using polylactic acid-glycolic acid copolymer and calcium phosphate material as raw materials. The bone defect repair material prepared by the present invention adopts high-temperature melting 3D printing technology, the raw materials are low-priced and easy to obtain, the processing method is low-cost, and the processing method is simple, convenient, and easy to use in hospital scenarios.

[0006] CN113289066A provides a composite material for repairing bone defects, which is prepared from polylactic acid, hydroxyapatite and lithium salt. The degradable bone defect repair scaffold made by 3D printing using the composite material as raw material can induce osteogenic activity and promote bone repair. It also has excellent mechanical strength and biocompatibility, excellent comprehensive performance, and has excellent application prospects in the field of bone repair. Summary of the invention

[0007] At present, polylactic acid-based biomimetic materials still have some shortcomings, such as insufficient toughness, rough surface of its products, etc., which greatly affect the processability of the composite material and the performance of the corresponding products. In order to overcome these shortcomings, on the one hand, the present invention provides a biomimetic material, which comprises: hydrophobically modified hydroxyapatite, polylactic acid, and a hyperbranched star polymer with a hyperbranched polymer structure as a core and polycaprolactone as an arm.

[0008] On the other hand, the present application provides a method for preparing a composition for biomimetic materials, which comprises the following steps: blending hydrophobically modified hydroxyapatite, polylactic acid and a hyperbranched star polymer with a hyperbranched polymer structure as a core and polycaprolactone as an arm, and then extruding to obtain the composition for biomimetic materials.

[0009] In another aspect, the present application provides a composition for bionic material prepared according to the preparation method of the present application.

[0010] On the other hand, the present application provides a biomimetic material product, which comprises the biomimetic material composition of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] For a more complete understanding of the present invention, reference should now be made to the embodiments shown in more detail in the accompanying drawings and described below by way of example of the invention, in which:

[0012] Figure 1 : (a) shows a transmission electron micrograph of unmodified hydroxyapatite; (b) shows a transmission electron micrograph of modified hydroxyapatite HA-1; (c) shows a transmission electron micrograph of modified hydroxyapatite HA-2. DETAILED DESCRIPTION

[0013] General Definitions and Terminology

[0014] Unless otherwise indicated, all publications, patent applications, patents, and other references mentioned herein are incorporated by reference in their entirety.

[0015] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. In the event of a conflict, the definitions provided herein shall prevail.

[0016] Unless otherwise indicated, all percentages, parts, ratios, etc. are by weight.

[0017] When quantity, concentration or other value or parameter is given as range, preferred range or preferred upper limit and lower limit or specific value, it should be understood as specifically disclosing all ranges formed by paired values ​​from any upper limit range or preferred value and any lower limit range or preferred value, regardless of whether the range is disclosed separately. Unless otherwise stated, when numerical range is quoted herein, the range refers to including its endpoints and integers and fractions within all such ranges. The scope of the present invention is not limited to the specific numerical value quoted when defining the range. For example, "1-8" covers 1, 2, 3, 4, 5, 6, 7, 8 and any sub-range consisting of any two values ​​therein, such as 2-6, 3-5.

[0018] The terms "about" and "approximately" when used with a numerical variable generally refer to the value of that variable and all values ​​of that variable are within experimental error (e.g., within a 95% confidence interval for the mean) or within ±10% of the specified value, or a wider range.

[0019] The terms "comprises", "includes", "has", "contains" or "involves" and other variations thereof herein are inclusive or open-ended and do not exclude other unlisted elements or method steps. It will be understood by those skilled in the art that the above terms such as "comprising" encompass the meaning of "consisting of". The expression "consisting of" excludes any element, step or ingredient not specified. The expression "consisting essentially of" means that the scope is limited to the specified elements, steps or ingredients, plus the optional presence of elements, steps or ingredients that do not substantially affect the basic and novel features of the claimed subject matter. It will be understood that the expression "comprising" encompasses the expressions "consisting essentially of" and "consisting of".

[0020] The term "selected from..." means that one or more elements in the group listed later are independently selected and may include combinations of two or more elements.

[0021] When values ​​or end-points of a range are described herein, it should be understood that the disclosure includes the specific value or end-point cited.

[0022] As used herein, the terms "one or more" or "at least one" refer to one, two, three, four, five, six, seven, eight, nine or more.

[0023] Unless otherwise specified, the terms "combination thereof" and "mixture thereof" refer to a multi-component mixture of the elements, such as a two-component mixture, a three-component mixture, a four-component mixture and the maximum possible multi-component mixture.

[0024] In addition, if the number of parts or components of the present invention is not indicated before, it means that there is no limit to the number of occurrences (or existence) of the parts or components. Therefore, it should be interpreted as including one or at least one, and the singular form of the parts or components also includes the plural form, unless the numerical value obviously represents the singular.

[0025] As used herein, the term "optional" or "optionally" means that the subsequently described event or circumstance may or may not occur, and that the description includes both occurring and not occurring of said event or circumstance.

[0026] When describing methods, components or steps, the use of letters or numbers is only for the purpose of distinction, and does not limit these methods, components or steps to be performed in the order or sequence of the identification. Those skilled in the art can make reasonable adjustments.

[0027] When the lower and upper limits of a numerical range are disclosed, any numerical value and any included range falling within the range are specifically disclosed. In particular, each range of values ​​disclosed herein (in the form of "about a to b", or equivalently, "approximately a to b", or equivalently, "about ab"), should be understood to represent each numerical value and range encompassed within the broader range.

[0028] The term "repeating unit" as used herein refers to a combination of atoms linked in a certain manner on a polymer chain, which is a basic unit constituting a polymer.

[0029] The term "number average molecular weight" as used herein is also referred to as the number average molar mass. j The mole fraction of the molecule is x j , the number of molecules is N j , then the number average molecular weight for

[0030]

[0031] in It can be determined by end group determination, gel chromatography, thin film osmotic pressure method, vapor osmotic pressure method, boiling point rise method, mass spectrometry and other methods. If not otherwise specified, the molecular weight described herein is the number average molecular weight. The number average molecular weight and its distribution of the present invention can be determined, for example, using a gel permeation chromatograph (GPC) or a mass spectrometer.

[0032] The term "room temperature" (RT) as used herein refers to about 20 to 35°C, preferably about 25°C.

[0033] In one aspect, the present application relates to a composition for biomimetic materials, comprising: hydrophobically modified hydroxyapatite, polylactic acid and a hyperbranched star polymer, wherein the hyperbranched star polymer has a hyperbranched polymer structure as a core and polycaprolactone as an arm.

[0034] As used herein, the term "biomimetic material" refers to a material that is designed to resemble a structure found naturally in an animal or human and / or to function in a manner similar to a structure found naturally in an animal or human.

[0035] Polylactic acid

[0036] In the biomimetic material composition of the present application, polylactic acid is the main component of the polymer matrix. The polylactic acid of the present application can be any one or more mixtures of left-handed polylactic acid (PLLA), right-handed polylactic acid (PDLA) and meso-polylactic acid (PDLLA). The polylactic acid of the present application is preferably left-handed polylactic acid, which has lower production cost and better biocompatibility than other types of polylactic acid.

[0037] The suitable molecular weight range of polylactic acid is conducive to making biomimetic material have excellent mechanical properties, and the number average molecular weight of the polylactic acid of the present application can be about 80,000-200,000, preferably about 150,000-170,000, for example, 80,000, 90,000, 100,000, 110,000, 120,000, 130,000, 140,000, 150,000, 160,000, 170,000, 180,000, 190,000, 200,000, etc. The molecular weight of polylactic acid is too low, and the mechanical properties of biomimetic material may decline, while the molecular weight of polylactic acid is too high, and the cost rises, and the fluidity of biomimetic material may deteriorate, which is unfavorable for the processing properties of material. The number average molecular weight described above is measured using gel permeation chromatography. The specific measuring method is as follows: polylactic acid is dissolved in chloroform with a concentration of 0.25 weight %, and polystyrene is used as a standard material, and the number average molecular weight of polylactic acid is obtained by gel permeation chromatography (instrument model: Viscotek TDA 305).

[0038] Hydrophobically modified hydroxyapatite

[0039] The chemical formula of hydroxyapatite (HA) is Ca 10 (PO4)6(OH)2 is the main inorganic component of human and animal bones and teeth. Its good biocompatibility, bioactivity, chemical stability, mechanical properties, etc. make it widely used in the field of bionic materials, especially in the field of bionic bone materials. Hydroxyapatite can promote the adhesion and proliferation of osteoblasts. Therefore, incorporating it into the polymer matrix can improve the hydrophilicity and bioactivity of PLA-based materials.

[0040] The term "hydrophobically modified hydroxyapatite" of the present application refers to hydroxyapatite modified by a hydrophobic modifier, and the hydrophilicity of the hydrophobically modified hydroxyapatite decreases compared to the hydroxyapatite that has not been hydrophobically modified. It should be understood that the "hydrophobically modified hydroxyapatite" of the present application is only used to indicate that its hydrophilicity is lower than that of the hydroxyapatite that has not been hydrophobically modified, and does not mean that the hydrophobically modified hydroxyapatite is a hydrophobic material. The strong hydrophilicity of hydroxyapatite may lead to its poor adhesion to the polylactic acid interface, resulting in poor compatibility between the two. The adhesion between the hydrophobically modified hydroxyapatite and the polylactic acid interface is enhanced, so the compatibility between the two is improved.

[0041] The hydrophobically modified hydroxyapatite of the present application may include one or more of the following groups: hydroxyapatite surface-modified by long-chain fatty acids, hydroxyapatite surface-modified by long-chain fatty alcohols. The hydroxyapatite surface-modified by long-chain fatty acids is hydroxyapatite whose surface has been hydrophobically modified by long-chain fatty acids. The hydroxyapatite surface-modified by long-chain fatty alcohols is hydroxyapatite whose surface has been hydrophobically modified by long-chain fatty alcohols. The modification process of hydroxyapatite by long-chain fatty acids or long-chain fatty alcohols refers to: the long-chain fatty acids or long-chain fatty alcohols form chemical bonds with the hydroxyl groups on the surface of hydroxyapatite through chemical reactions, so that the long-chain fatty acids or long-chain fatty alcohols are grafted on at least part of the surface of hydroxyapatite.

[0042] In the present application, long-chain fatty acids refer to fatty acids containing at least one straight chain of 5 or more carbon atoms. In the present application, long-chain fatty alcohols refer to fatty alcohols containing at least one straight chain of 5 or more carbon atoms. Compared with other hydrophobic modifiers that can be used for hydroxyapatite (such as silane coupling agents, fluorinated compounds, etc.), long-chain fatty acids and long-chain fatty alcohols have lower physiological toxicity and are conducive to application in biomimetic materials.

[0043] In addition, it is found in the present application that long-chain fatty acids and long-chain fatty alcohols have additional advantages in improving material properties. Without being bound by theory, the surface energy of hydroxyapatite particles is relatively high and they are prone to agglomeration, so it is difficult for hydroxyapatite particles to be evenly dispersed in an organic matrix, which is unfavorable to the performance of the material, for example, it may cause the surface roughness of biomimetic material products to be high, the performance of biomimetic material products to be uneven, etc. By using long-chain fatty acids or long-chain fatty acid alcohols to modify the surface of hydroxyapatite, the long-chain part can effectively increase the steric hindrance between hydroxyapatites and reduce agglomeration.

[0044] Considering the cost of raw materials and the reactivity, the preferred long-chain fatty acids include, but are not limited to, stearic acid, caprylic acid, oleic acid, lauric acid, myristic acid, palmitic acid or a combination thereof; the preferred long-chain fatty alcohols include, but are not limited to, stearyl alcohol, caprylic alcohol, oleyl alcohol, lauryl alcohol, myristyl alcohol, cetyl alcohol or a combination thereof. The hydroxyapatite surface-modified with stearic acid shows better hydrophobicity, chemical stability, thermal stability and other properties, and can more effectively reduce the agglomeration phenomenon, so that the hydroxyapatite particles can be dispersed more evenly in the organic matrix.

[0045] In the hydroxyapatite surface-modified by long-chain fatty acids of the present application, the weight ratio of hydroxyapatite to long-chain fatty acids can be 1:(0.1-0.2). In the hydroxyapatite surface-modified by long-chain fatty alcohols of the present application, the weight ratio of hydroxyapatite to long-chain fatty alcohols can be 1:(0.1-0.2). The above-mentioned weight ratio range can give a hydrophobically modified hydroxyapatite with desired hydrophilic / hydrophobic properties. In the hydrophobically modified hydroxyapatite, if the weight proportion of long-chain fatty acids or long-chain fatty alcohols is too high, it may be detrimental to the hydrophilicity of the biomimetic material; and if the weight proportion is too low, it is detrimental to the compatibility of the hydrophobically modified hydroxyapatite with the polymer matrix and its dispersibility in the polymer matrix.

[0046] In the present application, hydrophobically modified hydroxyapatite is a particle form, and its particle diameter can be nanometer scale. In one embodiment, the particle diameter range of hydrophobically modified hydroxyapatite can be about 25-125nm, preferably about 50-100nm, such as about 25nm, about 30nm, about 40nm, about 50nm, about 60nm, about 70nm, about 80nm, about 90nm, about 100nm, etc. The particle diameter of hydrophobically modified hydroxyapatite is too small, and its agglomeration effect will increase, which is unfavorable for the dispersibility of hydrophobically modified hydroxyapatite in polymer substrates, and in the process of preparing biomimetic material composition and subsequent processing / use thereof (such as in the process of 3D printing), the fluidity of the material may deteriorate, which is unfavorable for the processing performance of the material. And the particle diameter of hydrophobically modified hydroxyapatite is too high, and stress concentration points may be generated in biomimetic materials, which is susceptible to defects caused by external forces.

[0047] Hyperbranched star polymers

[0048] The hyperbranched star polymer of the present application has a hyperbranched polymer structure as a core and polycaprolactone as an arm.

[0049] Hyperbranched star polymers have multiple polycaprolactone arms. Polycaprolactone (PCL) has good biocompatibility and biodegradability, and also has good toughness. Therefore, when hyperbranched star polymers are blended with PLA, the polycaprolactone arms of the hyperbranched star polymers help improve the mechanical toughness of the material.

[0050] The number of arms of the hyperbranched star polymer can be 5-16, preferably 10-16, and more preferably 12. The number of polycaprolactone arms affects the proportion of polycaprolactone in the hyperbranched star polymer, and then affects the performance of the biomimetic material. In each arm of the hyperbranched star polymer, the suitable chain length of polycaprolactone is conducive to improving the performance of the biomimetic material, and the degree of polymerization of polycaprolactone in each arm is independently an integer selected from 15-150, preferably, the degree of polymerization of polycaprolactone in each arm is independently an integer selected from 20-100, for example, 15, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, etc. If the polymerization degree is too low, the chain length of the polycaprolactone arm is too short, which is not conducive to effectively improving the toughness of the material. If the polymerization degree is too high, the chain length of the polycaprolactone arm is too long, which is not conducive to its compatibility with PLA, resulting in degradation of the performance of the bionic material and may also deteriorate the fluidity of the bionic material, which is not conducive to the processing performance of the material.

[0051] Hyperbranched star polymers have a hyperbranched polymer structure as the core. A hyperbranched polymer structure refers to a structure that can be obtained by hyperbranched polymerization, which comprises a central core (also referred to as a core), branching units, and peripheral terminal functional groups. The core of the hyperbranched branched polymer structure is the starting point of the molecule, and branched segments consisting of branching units are formed by radiating outward from the core. Polycaprolactone is chemically bonded to the peripheral terminal functional groups of the hyperbranched polymer structure, thereby forming a star polymer with a hyperbranched polymer structure as the core and polycaprolactone as the arm.

[0052] Compared with linear polycaprolactone, the hyperbranched star polymer of the present application has lower viscosity, better biocompatibility and more active hydroxyl functional groups. The hyperbranched star polymer of the present application can significantly improve the performance of biomimetic materials. Without being bound by theory, the terminal hydroxyl groups of the hyperbranched star polymer (including: the terminal hydroxyl groups of the polycaprolactone arms and the terminal hydroxyl groups that may exist in the hyperbranched branched polymer structure) can form hydrogen bonds with the hydroxyl groups of hydroxyapatite, thereby improving the compatibility of PLA with hydroxyapatite.

[0053] In one embodiment, the core of the hyperbranched polymeric structure has the structure of Formula (I-1) or Formula (I-2):

[0054]

[0055] wherein a1, a2, a3, and a4 are each independently an integer selected from 1 to 5, preferably, a1, a2, a3, and a4 are all 1;

[0056]

[0057] Wherein, b1 is an integer selected from 0 to 10, and b2, b3 and b4 are each independently an integer selected from 1 to 5. Preferably, b1, b2, b3 and b4 are all 1.

[0058] In the above formulas (I-1) and (I-2), It indicates that the compound of formula (I-1) or (I-2) is connected to other parts in the hyperbranched polymer structure or to the polycaprolactone arm of the hyperbranched star polymer through a covalent bond at this site.

[0059] In one embodiment, in formula (I-1) The residue may be connected to a branching unit, to an H atom, or to a polycaprolactone arm. In a specific embodiment, The position is covalently linked to the carbonyl group in formula (II-1) or formula (II-2) to form an ester structure.

[0060] In one embodiment, in formula (I-2) The residue may be connected to a branching unit, to an H atom, or to a polycaprolactone arm. In a specific embodiment, the The position is covalently linked to the carbonyl group in formula (II-1) or formula (II-2) to form an ester structure.

[0061] In one embodiment, the branching unit of the branched polymeric structure has the structure of the following formula (II-1) or formula (II-2):

[0062]

[0063] Wherein, c1 and c2 are each independently an integer selected from 1 to 5, preferably, c1 and c2 are both 2;

[0064]

[0065] Wherein, d1 is an integer selected from 0 to 10, and d2 and d3 are each independently an integer selected from 1 to 5. Preferably, d1 is 0, and d2 and d3 are both 1.

[0066] In the above formulas (II-1) and (II-2), It indicates that the compound of formula (II-1) or (II-2) is connected to other parts in the hyperbranched polymer structure or to the polycaprolactone arm of the hyperbranched star polymer through a covalent bond at this position.

[0067] In one embodiment, in formula (II-1) The carbonyl group of formula (II-1) can be connected to the core of the hyperbranched structure, to other branching units, to H atoms, or to the polycaprolactone arms of the hyperbranched star polymer. The position is covalently connected to the oxygen atom in formula (I-1) or formula (I-2), or covalently connected to the oxygen atom in the "-O-" structure in another structure of formula (II-1), thereby forming an ester structure. In a specific embodiment, the oxygen atom side of the "-O-" structure in formula (II-1) Covalently linked to another carbonyl group in the structure of formula (II-1) to form an ester structure, or covalently linked to a polycaprolactone arm.

[0068] In one embodiment, in formula (II-2) The carbonyl group of formula (II-2) can be connected to the core of the hyperbranched structure, to other branching units, to H atoms, or to the polycaprolactone arms of the hyperbranched star polymer. The position is covalently connected to the oxygen atom in formula (I-1) or formula (I-2), or covalently connected to the oxygen atom in the "-O-" structure in another structure of formula (II-2), thereby forming an ester structure. In a specific embodiment, the oxygen atom side of the "-O-" structure in formula (II-2) Covalently linked to another carbonyl group in the structure of formula (II-2) to form an ester structure, or covalently linked to a polycaprolactone arm.

[0069] In the hyperbranched polymeric structure, the number of branching units can be 3-64, for example 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 30, 32, 35, 40, 45, 50, 55, 60, 64, etc.

[0070] In a specific embodiment, the core of the hyperbranched star polymer has the structure of the following formula (III-1), formula (III-2) or formula (III-3):

[0071]

[0072]

[0073] In the present application, it is unexpectedly found that hyperbranched star polymers are conducive to reducing the shrinkage of materials, which is not bound by theory, and this may be attributed to the three-dimensional topological structure in the hyperbranched star polymer. The lower shrinkage of the material is particularly advantageous for manufacturing corresponding products, especially biomimetic scaffolds. The lower shrinkage makes it possible to accurately control the size and fine structure of the biomimetic scaffold, avoiding significant changes in size and structure that affect the function of the biomimetic scaffold. The hyperbranched star polymers of the present application, particularly the hyperbranched star polymers with the above-mentioned preferred hyperbranched polymeric structure, can significantly reduce the shrinkage of biomimetic materials.

[0074] In the composition for biomimetic materials in the present application, the hydrophobically modified hydroxyapatite, polylactic acid and hyperbranched star polymer have a suitable component ratio, thereby giving the material excellent mechanical properties, desired biocompatibility, biodegradability, material processability, etc. Taking the total weight of the hydrophobically modified hydroxyapatite, polylactic acid and hyperbranched star polymer as 100 parts by weight: the content of polylactic acid can be 45-60 parts by weight, for example, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60 parts by weight, etc.; the content of the hydrophobically modified hydroxyapatite is 30-40 parts by weight, for example, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40 parts by weight, etc.; and the content of the hyperbranched star polymer is 5-20 parts by weight, for example, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 parts by weight, etc.

[0075] Preparation method of biomimetic material composition

[0076] On the other hand, the present application also includes a method for preparing a composition for biomimetic materials, which comprises the following steps: blending hydrophobically modified hydroxyapatite, polylactic acid, and a hyperbranched star polymer with a hyperbranched polymer structure as a core and polycaprolactone as an arm, and then extruding to obtain a composition for biomimetic materials.

[0077] The hydrophobically modified hydroxyapatite may be as defined above. The specific operation of hydrophobically modifying hydroxyapatite is not particularly limited, and for example, those known in the art may be used.

[0078] When long-chain fatty acids and / or long-chain fatty alcohols are used as hydrophobic modifiers, hydrophobically modified hydroxyapatite with desired hydrophilic / hydrophobic properties can be obtained by controlling the feed ratio of long-chain fatty acids and / or long-chain fatty alcohols to hydroxy fatty acids. In one embodiment, hydroxyapatite is surface-modified using long-chain fatty acids, and the weight ratio of hydroxyapatite to long-chain fatty acid feed can be 1:(0.1-0.2). In one embodiment, hydroxyapatite is surface-modified using long-chain fatty alcohols, and the weight ratio of hydroxyapatite to long-chain fatty alcohol feed can be 1:(0.1-0.2).

[0079] As an example, an embodiment of preparing hydroxyapatite surface-modified by stearic acid is shown below: 200g of hydroxyapatite is dispersed in 500ml of anhydrous ethanol, ultrasonically treated for 1h, and then heated to 60°C and stirred evenly to obtain hydroxyapatite slurry. 20g of stearic acid is dissolved in anhydrous ethanol at 60°C and added to the hydroxyapatite slurry, and the system is stirred at 60°C for 1h to modify the hydroxyapatite in a state dispersed in the system by reaction with stearic acid. After the modification is completed, the mixed solution is subjected to evaporation of anhydrous ethanol on a heating plate at 90°C to obtain a preliminarily dried hydrophobically modified hydroxyapatite, and then the preliminarily dried hydrophobically modified hydroxyapatite is further crushed and dried in a 90°C forced air dehumidification oven for 48h.

[0080] The hyperbranched star polymer of the present application can be prepared by the following steps: reacting a polyol with a branching monomer to obtain a terminal hydroxyl hyperbranched prepolymer; using the terminal hydroxyl hyperbranched prepolymer as an initiator to initiate the ring-opening polymerization of ε-caprolactone to obtain a hyperbranched star polymer.

[0081] In the process of obtaining the terminal hydroxyl hyperbranched prepolymer by reacting the polyol with the branching monomer, the hydroxyl in the polyol reacts with the functional group (carboxyl, ester group, etc.) of the branching monomer to form the first generation of terminal hydroxyl hyperbranched prepolymer. The terminal hydroxyl hyperbranched prepolymer of the first generation, its terminal hydroxyl group can further react with the free branching monomer to further form the second generation of terminal hydroxyl hyperbranched prepolymer, and so on. It is understood by those skilled in the art that in the process of preparing the terminal hydroxyl hyperbranched prepolymer, the reaction process of forming the dendritic terminal hydroxyl hyperbranched prepolymer is one of the ideal conditions, and in this preparation process, there is also the situation that some functional groups do not react to generate the terminal hydroxyl hyperbranched prepolymer with a certain degree of branching.

[0082] In one embodiment, the polyol is selected from the following formula (IV-1) and formula (IV-2):

[0083]

[0084] wherein a1', a2', a3', a4' are each independently an integer selected from 1 to 5, preferably, a1', a2', a3', a4' are all 1;

[0085]

[0086] Wherein, b1' is an integer selected from 0 to 10, and b2', b3', b4' are each independently an integer selected from 1 to 5. Preferably, b1', b2', b3', b4' are all 1.

[0087] In one embodiment, the branching monomer is selected from the following formula (V-1) and formula (V-2):

[0088]

[0089] wherein c1' and c2' are each independently an integer selected from 1 to 5 and c3' is an integer selected from 0 to 5, preferably, c1' and c2' are both 2 and c3' is 0;

[0090]

[0091] Wherein, d1′ is an integer selected from 0 to 10, and d2′ and d3′ are each independently an integer selected from 1 to 5. Preferably, d1′ is 0, and d2′ and d3′ are both 1.

[0092] In a preferred embodiment, the branching monomer is methyl N,N-dihydroxyethyl-3-aminopropionate (CAS No.: 118480-08-3) or 2,2-dihydroxymethylpropionic acid (CAS No.: 4767-03-7). In a more preferred embodiment, the branching monomer is methyl N,N-dihydroxyethyl-3-aminopropionate.

[0093] The terminal hydroxyl hyperbranched prepolymer of the desired structure is obtained by controlling the molar ratio of branched monomer to the polyol. In the present application, the molar ratio of branched monomer to the polyol can be about (28: 1) to (3: 1), such as about 28: 1, 26: 1, 24: 1, 21: 1, 20: 1, 15: 1, 14: 1, 12: 1, 10: 1, 9: 1, 8: 1, 6: 1, 5: 1, 4: 1, 3: 1, etc. This suitable molar ratio range is conducive to obtaining the terminal hydroxyl hyperbranched prepolymer of the desired structure, which has a suitable topological structure and the number of terminal hydroxyl groups, and can effectively initiate the ring-opening polymerization of ε-caprolactone. The reaction of polyol and branched monomer can be carried out in the presence of a catalyst. In one embodiment, polyol and branched monomer are carried out in the presence of a catalyst, and the catalyst includes: p-toluenesulfonic acid, methylsulfonic acid, phosphoric acid, zinc acetate, tetrapropyl titanate or a combination thereof. The catalyst can be used for about 0.01-0.5% of the weight of the branched monomer.

[0094] The appropriate reaction temperature of the polyol and the branching monomer is conducive to the hyperbranched polymerization reaction. The polyol and the branching monomer react at a temperature of about 100-130°C. Too high a reaction temperature may lead to decomposition of the raw materials and increase of by-products; too low a reaction temperature is not conducive to the smooth progress of the reaction.

[0095] In one embodiment, the hydroxyl-terminated hyperbranched prepolymer may have the structure of the following formula (VI-1):

[0096]

[0097] In one embodiment, the hydroxyl-terminated hyperbranched prepolymer may have the structure of the following formula (VI-2):

[0098]

[0099] In one embodiment, the hydroxyl-terminated hyperbranched prepolymer may have the structure of the following formula (VI-3):

[0100]

[0101] The terminal hydroxyl hyperbranched prepolymer serves as an initiator to initiate the ring-opening polymerization of ε-caprolactone, thereby forming a polycaprolactone segment connected to the terminal hydroxyl group of the terminal hydroxyl hyperbranched prepolymer, that is, forming a polycaprolactone arm.

[0102] The hydroxyl-terminated hyperbranched prepolymer can be used as an initiator to initiate the ring-opening polymerization of ε-caprolactone in the presence of a catalyst, and the catalyst can include but is not limited to tin catalysts, such as stannous octoate, stannous isooctanoate, etc. The amount of the catalyst can be about 0.1-0.5% by weight of the polycaprolactone.

[0103] The reaction temperature of the ring-opening polymerization of ε-caprolactone can be about 80-110° C. The reaction temperature of the ring-opening polymerization of ε-caprolactone can be about 5-12 hours. Appropriate reaction temperature and reaction time are helpful to obtain a smooth polymerization reaction and obtain the desired product.

[0104] The weight ratio of the terminal hydroxyl hyperbranched prepolymer to ε-caprolactone can be (1:10) to (1:30). If the weight ratio of the terminal hydroxyl hyperbranched prepolymer to ε-caprolactone is too low, it may lead to too high a proportion of polycaprolactone in the product or too high a chain length, which is not conducive to its compatibility with PLA, resulting in degradation of the performance of the bionic material, and may also make the fluidity of the bionic material worse, which is not conducive to the processing performance of the material; while if the weight ratio of the terminal hydroxyl hyperbranched prepolymer to ε-caprolactone is too low, the chain length of the polycaprolactone arm may be too short, which may not be conducive to improving the toughness of the material.

[0105] In the preparation method of the composition for biomimetic materials in the present application, the hydrophobically modified hydroxyapatite, polylactic acid and hyperbranched star polymer have a suitable feed ratio, thereby giving the material excellent mechanical properties, desired biocompatibility, biodegradability, material processability, etc. Taking the total weight of the hydrophobically modified hydroxyapatite, polylactic acid and hyperbranched star polymer as 100 parts by weight: the amount of polylactic acid can be 45-60 parts by weight, for example, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60 parts by weight, etc.; the amount of hydrophobically modified hydroxyapatite can be 30-40 parts by weight, for example, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40 parts by weight, etc.; and the amount of hyperbranched star polymer can be 5-20 parts by weight, for example, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 parts by weight, etc.

[0106] There is no particular limitation on the equipment used in the blending and extrusion process, and the process can be carried out using commonly used equipment in the art, including but not limited to a mixer, a twin-screw extruder, and the like.

[0107] In a specific embodiment, hydrophobically modified hydroxyapatite, polylactic acid, and a hyperbranched star polymer with a hyperbranched polymer structure as a core and polycaprolactone as an arm are uniformly stirred in a mixer and fed to a twin-screw extruder, and extruded and granulated by the twin-screw extruder to obtain a composition for biomimetic materials. The twin-screw extrusion temperature is about 190°C, the main engine speed is 300rpm, and the main feeding frequency is 10Hz.

[0108] In another aspect, the present application provides a composition for biomimetic materials prepared by the method of the present application.

[0109] Bionic material products

[0110] In another aspect, the present application provides a biomimetic material product comprising the biomimetic material composition described above.

[0111] The biomimetic material product may include the biomimetic material composition of the present application in whole or in part. For example, the biomimetic material product may be obtained by processing the biomimetic material composition in whole or in part.

[0112] There is no particular limitation on the processing method of the biomimetic material, for example, it can be 3D printing technology. The biomimetic material composition of the present application has suitable processing properties and is particularly suitable for 3D printing. For example, the biomimetic material can be made into a 3D printing wire and then used for 3D printing. The biomimetic material product of the present application can be a 3D printed product, that is, a product obtained by 3D printing technology.

[0113] There is no special restriction on the structural form of the bionic material product, and advantageously, it can be a bionic scaffold. The bionic scaffold of the present application exhibits excellent mechanical properties, biological activity, and the like.

[0114] An exemplary preparation method of a bionic scaffold is shown below: the bionic material composition is extruded into a 1.75 mm wire at 190° C. using a 3D printing wire extruder, and then the wire is printed into a bionic scaffold at a melting temperature of 200° C. using a 3D printer.

[0115] The biomimetic material composition of the present application has a suitable melt index range, which is particularly suitable for 3D printing. The melt index of the biomimetic material composition of the present application can be measured using a melt index tester (MFI-1211) with reference to GB / T3682-2000. Under the conditions of 190°C measuring temperature and a load of 2.16kg, the melt index of the biomimetic material composition of the present application can be about 6-25g / 10min, for example, about 6g / 10min, 7g / 10min, 8g / 10min, 9g / 10min, 10g / 10min, 11g / 10min, 12g / 10min, 13g / 10min, 14g / 10min, 15g / 10min, 16g / 10min, 17g / 10min, 18g / 10min, 19g / 10min, 20g / 10min, etc.

[0116] The bionic material product of the present application has excellent mechanical properties, which can be evaluated by tensile strength, elongation at break and notched impact strength.

[0117] Elongation at break: generally used is the relative elongation at break, that is, the ratio of the elongation of the bionic material product at break to its initial length, expressed as a percentage. The elongation at break of the bionic material product can be measured using conventional methods in the art, such as by testing the ASTM D638 standard tensile specimen obtained by 3D printing. The elongation at break of the bionic material product of the present application is about 2-10%, for example, about 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc.

[0118] Tensile strength: Characterizes the resistance of the material to the maximum uniform plastic deformation. Before the tensile specimen is subjected to the maximum tensile stress, the deformation is uniform and consistent, but after exceeding the maximum tensile stress, necking begins to occur, that is, concentrated deformation occurs; for brittle materials with no (or very little) uniform plastic deformation, it reflects the material's resistance to fracture. The tensile strength of bionic material products can be measured using conventional methods in the art, such as by testing the ASTM D638 standard tensile specimens obtained by 3D printing. The tensile strength of the bionic material product of the present invention is about 20-100MPa, for example, about 20MPa, 30MPa, 40MPa, 50MPa, 55MPa, 60MPa, 70MPa, 80MPa, 90MPa, 100MPa, etc.

[0119] The notched impact strength can characterize the impact load resistance of the biomimetic material product. The impact strength of the biomimetic material product can be measured using conventional methods in the art, such as by testing using ASTM D1288 standard impact specimens obtained by 3D printing. The notched impact strength of the biomimetic material product of the present invention is about 2-10 KJ / m 2 , for example, about 2KJ / m 2 , 2.5KJ / m 2 、3KJ / m 2 、3.5KJ / m 2 , 4KJ / m 2 4.5KJ / m 2 , 5KJ / m 2 5.5KJ / m 2 , 6KJ / m 2 , 7KJ / m 2 , 8KJ / m 2 , 9KJ / m 2 、10KJ / m 2 wait.

[0120] The shrinkage rate of the bionic material product refers to the percentage of the difference between the ideal size and the actual size in the ideal size, which reflects the reduction degree of the product relative to the expected size during the molding process. The shrinkage rate of the bionic material product of the present application can be tested according to the test standard GB / T15585-1995 "Determination of the shrinkage rate of thermoplastic injection molding". The calculation formula of the shrinkage rate is: shrinkage rate = (ideal size-actual size) / ideal size × 100%. The shrinkage rate of the bionic material product of the present application can be below 0.50%, for example, below 0.50%, below 0.45%, below 0.40%, below 0.35%, below 0.30%, below 0.25%, below 0.20%, below 0.15%, etc.

[0121] The 3D printing wire made of the bionic material of the present application has good toughness and high surface quality. The bionic scaffold obtained by 3D printing with the 3D printing wire has good mechanical properties, good dimensional stability and a smooth printing process.

[0122] Beneficial Effects

[0123] The present invention improves the compatibility of hydroxyapatite with a polymer matrix by surface modification of hydroxyapatite, and long-chain fatty acids (alcohols) as hydrophobic modifiers can effectively increase the steric hindrance between hydroxyapatite, reduce agglomeration, and make hydroxyapatite more dispersed in polymers. The present invention creatively introduces a hyperbranched star polymer with a hyperbranched polymer structure as a core and polycaprolactone as an arm into a PLA / HA composite system to further improve system performance. The hyperbranched star polymer can effectively improve the compatibility between the components and can also reduce the shrinkage of the biomimetic material composition. The present application biomimetic material composition can be processed to obtain a 3D printing wire with good toughness and high surface quality. The 3D printing wire is made by 3D printing technology, and the obtained biomimetic scaffold has good mechanical properties, good dimensional stability, and a smooth printing process.

[0124] Example

[0125] The solution of the present invention is further described in detail below in conjunction with specific embodiments.

[0126] It should be noted that the following examples are merely examples for clearly illustrating the technical solutions of the present invention, and are not intended to limit the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description, and it is not necessary and impossible to exhaustively list all the embodiments here, and the obvious changes or modifications derived therefrom are still within the scope of protection of the present invention. Unless otherwise specified, the instruments, equipment, and reagents used herein are all commercially available.

[0127] Material

[0128] preparation

[0129] Preparation of hydrophobically modified hydroxyapatite

[0130] Hydrophobically modified hydroxyapatite HA-1

[0131] 200g of hydroxyapatite (purchased from Anhui Tongfenghe Biotechnology Co., Ltd., particle size 50nm) was dispersed in 500ml of anhydrous ethanol, ultrasonically treated for 1h, then heated to 60°C and stirred evenly to obtain hydroxyapatite slurry. 20g of stearic acid was dissolved in anhydrous ethanol at 60°C and added to the hydroxyapatite slurry. The system was stirred at 60°C for 1h to modify the hydroxyapatite by reacting with stearic acid in a state dispersed in the system. After the modification was completed, the mixed solution was evaporated on a heating plate at 90°C to obtain a preliminarily dried hydrophobically modified hydroxyapatite. Subsequently, the preliminarily dried hydrophobically modified hydroxyapatite was further crushed and dried in a 90°C blast dehumidification oven for 48h to obtain a fully dried hydrophobically modified hydroxyapatite HA-1 surface-modified with stearic acid.

[0132] Hydrophobically modified hydroxyapatite HA-2

[0133] 200g of hydroxyapatite (purchased from Anhui Tongfenghe Biotechnology Co., Ltd., particle size 50nm) was dispersed in 500ml of anhydrous ethanol, ultrasonically treated for 1h, then heated to 60°C and stirred evenly to obtain hydroxyapatite slurry. 40g of stearic acid was dissolved in anhydrous ethanol at 60°C and added to the hydroxyapatite slurry. The system was stirred at 60°C for 1h to modify the hydroxyapatite by reacting with stearic acid in a state dispersed in the system. After the modification was completed, the mixed solution was evaporated on a heating plate at 90°C to obtain a preliminarily dried hydrophobically modified hydroxyapatite, and then the preliminarily dried hydrophobically modified hydroxyapatite was further crushed and dried in a 90°C blast dehumidification oven for 48h to obtain a fully dried hydrophobically modified hydroxyapatite HA-2 surface-modified with stearic acid.

[0134] Take a small amount of unmodified hydroxyapatite to be tested (purchased from Anhui Tongfenghe Biotechnology Co., Ltd., particle size 50nm) and the above-prepared hydrophobically modified hydroxyapatite HA-1 and HA-2, respectively, and add them to anhydrous ethanol to prepare 3 parts of suspensions with a solid content of about 0.0.1%. After ultrasonic dispersion of the suspension for 2h, add it dropwise to the sample stage. After the ethanol evaporates, spray gold on the surface of the sample stage for 60s. After the spraying is completed, use SEM to observe.

[0135] Figure 1 (a) shows a transmission electron micrograph of unmodified hydroxyapatite, Figure 1 (b) shows a transmission electron micrograph of modified hydroxyapatite HA-1, Figure 1 (c) shows the transmission electron micrograph of the modified hydroxyapatite HA-2. From the transmission electron micrograph, it can be seen that the unmodified hydroxyapatite has poor dispersibility and obvious agglomeration. However, the modified hydroxyapatites HA-1 and HA-2 both have excellent dispersibility.

[0136] Preparation of hyperbranched star polymers

[0137] 1. Preparation of hydroxyl-terminated hyperbranched prepolymers

[0138] Hydroxyl-terminated hyperbranched prepolymer G1-(OH)6

[0139] At room temperature, 15 g of trihydroxymethylpropane, 64.14 g of branched monomer (N,N-dihydroxyethyl-3-aminopropionic acid methyl ester) and 0.32 g of p-toluenesulfonic acid were added to a flask, the system was heated to 120°C, and reacted at this temperature for 3 hours. The system was vacuum dried to obtain a yellow transparent oily liquid terminal hydroxyl hyperbranched prepolymer G1-(OH)6.

[0140] Hydroxyl-terminated hyperbranched prepolymer G2-(OH)12

[0141] At room temperature, 15 g of trihydroxymethylpropane, 64.14 g of branching monomer (N, N-dihydroxyethyl-3-aminopropionic acid methyl ester) and 0.32 g of p-toluenesulfonic acid were added to a flask, the system was heated to 120°C, and reacted at this temperature for 3 hours, and the system was vacuumed to remove the generated methanol. Subsequently, 128.28 g of branching monomer (N, N-dihydroxyethyl-3-aminopropionic acid methyl ester) and 0.64 g of p-toluenesulfonic acid were added to the system, and after reacting at a temperature of 120°C for 3 hours, the system was vacuumed and dried to obtain a yellow transparent oily liquid terminal hydroxyl hyperbranched prepolymer G2-(OH)12.

[0142] Hydroxyl-terminated hyperbranched prepolymer G3-(OH)24

[0143] At room temperature, 15 g of trihydroxymethylpropane, 64.14 g of branching monomer (N, N-dihydroxyethyl-3-aminopropionic acid methyl ester) and 0.32 g of p-toluenesulfonic acid were added to the flask, the system was heated to 120 ° C, and reacted at this temperature for 3 hours, and the system was vacuumed to remove the generated methanol. Subsequently, 128.28 g of branching monomer (N, N-dihydroxyethyl-3-aminopropionic acid methyl ester) and 0.64 g of p-toluenesulfonic acid were added to the system, and after reacting at a temperature of 120 ° C for 3 hours, the system was vacuumed and dried. Finally, 256.56 g of branching monomer (N, N-dihydroxyethyl-3-aminopropionic acid methyl ester) and 1.28 g of p-toluenesulfonic acid were added to the system, and after reacting at a temperature of 120 ° C for 4 hours, the system was vacuumed and dried to obtain a yellow transparent oily liquid terminal hydroxyl hyperbranched prepolymer G3-(OH)24.

[0144] 2. Add the prepared hydroxyl-terminated hyperbranched prepolymer and ε-caprolactone (the raw material type and weight ratio of the feed are shown in Table 1 below) into a round-bottom flask, and react for 8 hours at 100°C under N2 environment and stannous isooctanoate as a catalyst. After the reaction, a transparent oily liquid is obtained, which is a white solid after being cooled and solidified. The white solid is repeatedly washed with distilled water, and then methanol is used as a precipitant to obtain a white precipitate, which is a hyperbranched star polymer.

[0145] Table 1

[0146]

[0147] Examples 1-12

[0148] According to the amounts shown in Table 2, the above-prepared hydrophobically modified hydroxyapatite HA-1, polylactic acid (purchased from Zhejiang Haizheng Biomaterial Co., Ltd., with a molecular weight of about 150,000, brand R110) and the prepared hyperbranched star polymer were mixed evenly by a stirrer, and extruded into granules by a twin-screw extruder, wherein the twin-screw extrusion temperature was 190° C., the main engine speed was 300 rpm, and the main feeding frequency was 10 Hz, to obtain samples of Examples 1-12.

[0149] Table 1

[0150]

[0151] Comparative Example 1

[0152] 40 parts by weight of unhydrophobically modified hydroxyapatite (purchased from Anhui Tongfenghe Biotechnology Co., Ltd., with a particle size of 50 nm) and 60 parts by weight of polylactic acid (purchased from Zhejiang Haizheng Biomaterials Co., Ltd., with a molecular weight of about 150,000, brand R110) were mixed evenly with a stirrer and extruded into granules through a twin-screw extruder, wherein the twin-screw extrusion temperature was 190°C, the main engine speed was 300 rpm, and the main feeding frequency was 10 Hz to obtain the sample of Comparative Example 1.

[0153] Comparative Example 2

[0154] 40 parts by weight of the hydrophobically modified hydroxyapatite HA-1 prepared above and 60 parts by weight of polylactic acid (purchased from Zhejiang Haizheng Biomaterials Co., Ltd., with a molecular weight of about 150,000, brand R110) were mixed evenly by a stirrer and extruded into granules by a twin-screw extruder, wherein the twin-screw extrusion temperature was 190°C, the main engine speed was 300rpm, and the main feeding frequency was 10Hz, to obtain the sample of Comparative Example 2.

[0155] Comparative Example 3

[0156] 10 parts by weight of linear polycaprolactone, 36 parts by weight of the above-prepared hydrophobically modified hydroxyapatite HA-1 and 54 parts by weight of polylactic acid (purchased from Zhejiang Haizheng Biomaterials Co., Ltd., with a molecular weight of about 150,000, brand R110) were mixed evenly by a stirrer and extruded into granules by a twin-screw extruder, wherein the twin-screw extrusion temperature was 190°C, the main engine speed was 300rpm, and the main feeding frequency was 10Hz to obtain a sample of Comparative Example 3.

[0157] Comparative Example 4

[0158] 10 parts by weight of a hyperbranched star polymer numbered P5, 36 parts by weight of non-hydrophobically modified hydroxyapatite (purchased from Anhui Tongfenghe Biotechnology Co., Ltd., with a particle size of 50 nm) and 54 parts by weight of polylactic acid (purchased from Zhejiang Haizheng Biomaterials Co., Ltd., with a molecular weight of about 150,000, brand R110) were mixed evenly by a stirrer and extruded into granules by a twin-screw extruder, wherein the twin-screw extrusion temperature was 190°C, the main engine speed was 300rpm, and the main feeding frequency was 10Hz, to obtain the sample of Comparative Example 4.

[0159] Performance Testing

[0160] The samples of the embodiment and the comparative example were extruded into 1.75 mm wires at 190° C. using a 3D printing wire extruder, and then the wires were printed into mechanical property specimens at a melting temperature of 200° C. using a 3D printer. The specimens of the embodiment and the comparative example were tested according to the following test method.

[0161] Melt index: The samples of the examples and comparative examples were measured at 190° C. and a load of 2.16 kg; instrument: Melt index tester (MFI-1211).

[0162] Tensile strength: The test was conducted using 3D printed ASTM D638 standard tensile specimens with a tensile rate of 50 mm / min. The instrument model was WDW3020 from Changchun Kexin Testing Instrument Company.

[0163] Elongation at break: The test was conducted using ASTM D638 standard tensile specimens obtained by 3D printing, with a tensile rate of 50 mm / min. The instrument model was WDW3020 from Changchun Kexin Testing Instrument Company.

[0164] Notched impact strength: The test was conducted using ASTM D1288 standard impact specimens obtained by 3D printing; the instrument model was XJJUD-50Q from Qixiang Company.

[0165] Shrinkage rate: The shrinkage rate of the material is characterized by the test standard GB / T15585-1995 "Determination of shrinkage rate of thermoplastic injection molding". The actual size of the 3D printed spline is measured with a vernier caliper. Shrinkage rate = (ideal size - actual size) / ideal size × 100%.

[0166] Table 3

[0167]

[0168] As can be seen from Table 3, the samples of the embodiments of the present application have a suitable melt index range and are suitable for 3D printing. The samples of the embodiments of the present application also have excellent mechanical properties and low shrinkage. In addition, the corresponding composition samples obtained from the hyperbranched star polymers prepared from the terminal hydroxyl hyperbranched prepolymers G2-(OH)12 and G3-(OH)24 as raw materials have better overall performance.

[0169] It can be seen from Comparative Examples 1-2 that the fluidity of the system containing only polylactic acid and hydroxyapatite is poor. According to the comparison of the test data of Comparative Example 3 with Examples 1-4, 6, 9-12, it can be found that the addition of hyperbranched star polymers to the PLA / HA system helps to improve the fluidity and mechanical properties of the material system, and is also conducive to reducing the shrinkage rate. According to the comparison of Comparative Example 4 with Example 6, it can be found that by hydrophobic modification of hydroxyapatite, the performance of the material can be further improved.

[0170] The above embodiments are only intended to introduce preferred embodiments of the present invention. For those skilled in the art, any obvious changes and improvements made without departing from the spirit of the present invention should be regarded as part of the present invention.

Claims

1. A biomimetic material composition comprising: Hydrophobically modified hydroxyapatite, Polylactic acid, and Hyperbranched star polymer with a hyperbranched polymer structure as the core and polycaprolactone as the arms.

2. The biomimetic material composition according to claim 1, wherein The hydrophobically modified hydroxyapatite is selected from: hydroxyapatite surface-modified by long-chain fatty acids, hydroxyapatite surface-modified by long-chain fatty alcohols, and combinations thereof; Preferably, The long-chain fatty acids include stearic acid, caprylic acid, oleic acid, lauric acid, myristic acid, palmitic acid or a combination thereof. The long-chain fatty alcohols include: stearyl alcohol, capryl alcohol, oleyl alcohol, lauryl alcohol, myristyl alcohol, cetyl alcohol or a combination thereof; More preferably, The hydrophobically modified hydroxyapatite is hydroxyapatite surface-modified by stearic acid.

3. The biomimetic material composition according to claim 2, wherein: In the hydroxyapatite surface-modified with long-chain fatty acids, the weight ratio of hydroxyapatite to long-chain fatty acids is 1:(0.1-0.2); In the hydroxyapatite surface-modified with long-chain fatty alcohol, the weight ratio of hydroxyapatite to long-chain fatty alcohol is 1:(0.1-0.2).

4. The biomimetic material composition according to any one of claims 1 to 3, wherein The core of the hyperbranched polymeric structure has the structure of the following formula (I-1) or formula (I-2): wherein a1, a2, a3, and a4 are each independently an integer selected from 1 to 5, preferably, a1, a2, a3, and a4 are all 1; wherein b1 is an integer selected from 0 to 10, and b2, b3 and b4 are each independently an integer selected from 1 to 5, preferably, b1, b2, b3 and b4 are all 1; and, The branching unit of the hyperbranched polymer structure has the structure of the following formula (II-1) or formula (II-2): Wherein, c1 and c2 are each independently an integer selected from 1 to 5, preferably, c1 and c2 are both 2; Wherein, d1 is an integer selected from 0 to 10, and d2 and d3 are each independently an integer selected from 1 to 5. Preferably, d1 is 0, and d2 and d3 are both 1.

5. The biomimetic material composition according to claim 4, wherein: The number of branching units in the hyperbranched polymeric structure is 3-64.

6. The biomimetic material composition according to any one of claims 1 to 5, wherein The core of the hyperbranched star polymer has a structure of the following formula (III-1), formula (III-2) or formula (III-3):

7. The biomimetic material composition according to any one of claims 1 to 6, wherein The number of arms of the hyperbranched star polymer is 5-16, preferably 10-16, more preferably 12; and / or The degree of polymerization of polycaprolactone in each arm of the hyperbranched star polymer is independently an integer selected from 15-150; and / or The polylactic acid is selected from the group consisting of L-polylactic acid, D-polylactic acid, meso-polylactic acid and combinations thereof, preferably L-polylactic acid; and / or The number average molecular weight of the polylactic acid is 80,000-200,000, preferably 150,000-170,000; and / or The particle size of the hydrophobically modified hydroxyapatite is in the range of 25-125 nm, preferably 50-100 nm.

8. The biomimetic material composition according to any one of claims 1 to 7, wherein Taking the total weight of the hydrophobically modified hydroxyapatite, polylactic acid and hyperbranched star polymer as 100 parts by weight: The content of the polylactic acid is 45-60 parts by weight; The content of the hydrophobically modified hydroxyapatite is 30-40 parts by weight; and The content of the hyperbranched star polymer is 5-20 parts by weight.

9. A method for preparing a biomimetic material composition, comprising the following steps: The hydrophobically modified hydroxyapatite, polylactic acid and a hyperbranched star polymer with a hyperbranched polymer structure as a core and polycaprolactone as an arm are mixed and extruded to obtain the biomimetic material composition.

10. The method of claim 9, wherein: The hyperbranched star polymer is prepared by the following steps: reacting a polyol with a branching monomer to obtain a hydroxyl-terminated hyperbranched prepolymer; The terminal hydroxyl hyperbranched prepolymer is used as an initiator to initiate the ring-opening polymerization of ε-caprolactone to obtain the hyperbranched star polymer.

11. The method of claim 10, wherein: The polyol is selected from the following formula (IV-1) and formula (IV-2): wherein a1', a2', a3', a4' are each independently an integer selected from 1 to 5, preferably, a1', a2', a3', a4' are all 1; Wherein, b1' is an integer selected from 0 to 10, and b2', b3', b4' are each independently an integer selected from 1 to 5, preferably, b1', b2', b3', b4' are all 1; and, The branched monomer is selected from the following formula (V-1) and formula (V-2): wherein c1' and c2' are each independently an integer selected from 1 to 5 and c3' is an integer selected from 0 to 5, preferably, c1' and c2' are both 2 and c3' is 0; Wherein, d1′ is an integer selected from 0 to 10, and d2′ and d3′ are each independently an integer selected from 1 to 5. Preferably, d1′ is 0, and d2′ and d3′ are both 1.

12. The method according to claim 10 or 11, wherein The molar ratio of the branching monomer to the polyol is from (3:1) to (28:1); and / or The reaction of the polyol and the branching monomer is carried out in the presence of a catalyst, wherein the catalyst comprises p-toluenesulfonic acid, methanesulfonic acid, phosphoric acid, zinc acetate, tetrapropyl titanate or a combination thereof; and / or The weight ratio of the terminal hydroxyl hyperbranched prepolymer to the ε-caprolactone is (1:10) to (1:30); and / or The reaction temperature of the terminal hydroxyl hyperbranched prepolymer and the ε-caprolactone is 100-130° C.; and / or. The reaction time of the terminal hydroxyl hyperbranched prepolymer and the ε-caprolactone is 5-12 hours.

13. A composition for biomimetic material, prepared by the method according to any one of claims 9 to 12.

14. A biomimetic material product, comprising the biomimetic material composition according to any one of claims 1 to 8 or 13; Preferably, The bionic material product is a bionic stent; and / or The bionic material product is a 3D printed product.

Citation Information

Patent Citations

  • Composite material for repairing bone defect and preparation method thereof

    CN113289066A

  • 3D printing medical PLA (polylactic acid) / PCL (polycaprolactone) blend resin and preparation method thereof

    CN108727791A

  • Elastomeric and degradable high-mineral content polymer composites

    US20140088618A1

Cited By

  • Calcium phosphate-polycaprolactone composite scaffold and preparation method and application thereof

    CN122351600A

  • A polycaprolactone composite stent and a preparation method and application thereof

    CN122786564A